Revenue Equivalence and Bidding Behavior in a Multi-Unit Auction Market: An Empirical Analysis - Tenorio, Rafael (The Review of Economics and Statistics, 1993)
Revenue-equivalence of competitive and discriminatory formats is a major result for private-value multiunit auctions with risk-neutral bidders. Among the factors that may cause this result to break down, the most notorious ones are risk-aversion, value-affiliation, and endogenous bidder participation. Using data from competitive and discriminatory auctions undertaken in the Zambian foreign exchange market, the author analyzes revenue-equivalence and other bidding phenomena. The results indicate that (1) competitive auctions were revenue-superior due to higher participation; (2) high bidders adjusted with delay to an auction format change; and (3) a reservation bid was used as a policy instrument. Copyright 1993 by MIT Press.